Confidential print Borneo and Sulu 1884-1888 (Great Britain : Public Record Office, 1971)
Mengandungi hal-hal berkaitan perkapalan; laporan mesyuarat; charter of the British North Borneo Co.; anggaran Jabatan Kementerian Luar; pengumuman kerajaan berkaitan buruh asing;'Further correspondence respecting the affair of Sulu and the concessions of Territory in Borneo to Messrs Dent and Overbeck 1882-86; dll.